2022
DOI: 10.3390/jcm11195543
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Count and Neutrophil-to-Lymphocyte Ratio Are Associated with Mild Cognitive Impairment in Parkinson’s Disease: A Single-Center Longitudinal Study

Abstract: Lymphocyte count and neutrophil-to-lymphocyte ratio (NLR) may represent useful biomarkers of Parkinson’s disease (PD), but their role in PD-related mild cognitive impairment (MCI) has not been fully elucidated. The present study aimed to confirm whether these immunological measures can discriminate PD patients from healthy controls (HC) and establish their feasibility as prognostic biomarkers of MCI in PD. Immunological data at baseline were analyzed in 58 drug-naïve PD patients and 58 HC matched 1:1 for age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
(46 reference statements)
2
4
0
Order By: Relevance
“…A recent prospective study found that individuals with gastrointestinal symptoms that required a gastrointestinal endoscopy, but with a finding of histologically normal mucosa or nonspecific inflammation, had an increased subsequent risk of developing Alzheimer's or Parkinson diseases compared with the population references [70]. In line with this are previously published studies in which lymphocyte count and different patterns of neutrophil-to-lymphocyte or platelet-to-lymphocyte ratio were associated not only with PD, but also with MCI in PD or MSA patients, thus reflecting the inflammatory process in α-synucleinopathies [71,72].…”
Section: Plasma Oxidative Stress Index In Patients At Risk Of Develop...supporting
confidence: 73%
“…A recent prospective study found that individuals with gastrointestinal symptoms that required a gastrointestinal endoscopy, but with a finding of histologically normal mucosa or nonspecific inflammation, had an increased subsequent risk of developing Alzheimer's or Parkinson diseases compared with the population references [70]. In line with this are previously published studies in which lymphocyte count and different patterns of neutrophil-to-lymphocyte or platelet-to-lymphocyte ratio were associated not only with PD, but also with MCI in PD or MSA patients, thus reflecting the inflammatory process in α-synucleinopathies [71,72].…”
Section: Plasma Oxidative Stress Index In Patients At Risk Of Develop...supporting
confidence: 73%
“…In contrast, a case–control study by Sağlam Aykut et al (2018) reported a negative correlation between cognitive function and the NLR. In addition, other studies have shown that NLR values were significantly lower in Parkinson’s disease patients with MCI compared with those without MCI ( Contaldi et al, 2022 ). The differences in results may be due to differences in sample size, age, disease, and scales that measure cognitive function.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, markers related to peripheral blood neutrophils can predict a decrease in executive function in patients with AD ( 54 ). A recent study indicated that an elevated NLR is associated with cognitive impairment in PD patients ( 55 ). Therefore, we explored the potential of the NLR as a biomarker.…”
Section: Discussionmentioning
confidence: 99%